The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages war provided serious shocks for the complacent. First, the condition of the children on arrival in reception areas, a large proportion verminous and ill-clad, with unhealthy feeding and other habits. This aroused public interest in the town conditions under which these children were reared, and many people became aware for the first time that thousands of women have no sinks or running water and no proper cooking facilities in their homes. The dependence of the townspeople on the cinema and the excitement of the streets was revealed, as was the absence for many people, both from town and country, of a satisfactory social life. The backwardness of many local authorities in country districts with regard to the provision of adequate health services, school accommodation and so forth also became apparent. Enough has however been written elsewhere of the defects of the evacuation scheme, and the reasons for its partial failure, and it is not proposed to enlarge on them here. In the places where evacuation was a success, the good effect of country life on the children was striking. Weights and heights increased, children learned to sleep in quiet at the proper time and to eat good food decently, and to form other desirable social habits impossible of acquisition in their own homes. Much more might have been achieved. We might have had all over the country, holiday camps and hostels which could have been used for holidays 6 15X/2/464/1